Theoterrorism v. freedom of speech : from incident to precedent - Cliteur, P. B. (Amsterdam University Press, 2019)
"The Rushdie Affair, the Danish Cartoon Affair, the assault on Charlie Hebdo, and the earlier Carrell Affair, are examples of religious fanatics'extreme reactions to religious satire and criticism. Perpetrators of these actions consider themselves as true believers. This book aims to understand their motives by means of the concept of theoterrorism: terrorism grounded in religious zealotry"--Publisher's description